A Packaged and Reusable Hydrogel Strain Sensor with Conformal Adhesion to Skin for Human Motions Monitoring (Adv. Mater. Interfaces 6/2022). Issue 6 (23rd February 2022) - Zhao, Meijin; Zhang, Wenshuai; Wang, Dan; Sun, Peipei; Tao, Yuanyuan; Xu, Lingxiao; Shi, Lei
Abstract : Hydrogel Strain Sensor In article number 2101786, Meijin Zhao, Lingxiao Xu, Lei Shi, and co‐workers use photopolymerizable hydrogel as external packaging layer for hydrogel conducting wires bearing linear sensing property. The inhibition of water evaporation by packaging strategy endows the hydrogel sensor with enhanced lifespan. Besides, the sensor exhibits good reusability benefiting from the swelling property of external hydrogel film.